Transformasi Kapitalisme Perdesaan: dari Agraria ke Ekonomi Kreatif - Zamzam Muhammad Fuad (LPPM Stikosa - AWS, 2022)
Internet has changed socio-economic Indonesia to the rural level. This article show that Indonesia, especially in the rural area, transformed from an agrarian economy to a creative and trade economy. This article uses a qualitative method by combining observation and desk study. The results of this study show that the demographic bonus and the internet has encouraged rural capitalism which is no longer focused on the agrarian sector but has begun to shift to the creative economy sector and trade in goods. However, the emergence of this new capitalist is not guarantee the dawn of an independent economic sector. Ironically the development of the digital economy in rural areas may even lead to a economic which is depend to the import goods.